헤테로토피아적 장소연구 - 동대문디자인플라자를 중심으로 - 공현진; Kong Hyun Jin; 양태근; Yang Tae Keun (기초조형학연구, 2019)
본 연구는 프랑스 철학자 미셸 푸코의 공간이론 ‘헤테로토피아’ 개념을 통해 이라크 건축가 자하 하디드가 설립한 ‘동대문디자인플라자’를 중심으로, 과거의 동대문 터가 함축하고 있었던 역사에 대한 변화상과 장소의 미학을 탐구한다. 이와 같은 담론을 구축하기 위해 과거 조선 시대부터 형성된 동대문 장소의 기억들을 관련 유적과 전시물을 통해 살펴보고, 이를 기반으로 한 장소탐구의 미학적 방법론을 3가지의 틀을 통해 고찰한다. 이 과정에서 얻은 결과로 첫째, 동대문디자인플라자 터는 지형적 단점을 물리적으로 극복하기 위해 군사적 요충지로 기능이 탈바꿈된 열림과 닫힘의 헤테로토피아였으며, 둘째, 이간수문과 성벽 유적은 과거의 터를 아끼고 지키려 했던 선조들의 긍정적 욕망이 중첩된 장소로 해석할 수 있다. 마지막으로 일제에 의해 종합운동장으로 건립되었던 과거 경성운동장의 출현은 식민지 시대의 일제에 의해 조정된 한시적 유토피아의 건설이었다는 점을 유추할 수 있다. 덧붙여 자하 하디드의 동대문디자인플라자 건축물이 오늘날 해체주의적 노마디즘의 특성을 띠고 있다는 선행연구에서 그 형식미학에 대해 살펴보며, 이것이 오늘날 동시대의 풍경과 어떻게 공존하고 있는지에 대한 증거를 미술사에서 바로크적인 시선으로 살펴보고자 했다. 결과적으로 이러한 형식미가 깃든 동대문디자인플라자는 특정 장소를 정치화하여 이용하려는 현상으로 인해 구축된 유토피아적 장소의 사례로 간주할 수 있음을 확인하였다. This study aims to explore the historic change aspect and aesthetics of place that the past Dongdaemun (East Gate) site implies, focused on the Dongdaemun Design Plaza built by Iraqi architect Zaha Hadid through French philosopher Michel Foucault’s spatial theory, Heterotopia. To build such a study discourse, this study examined the Dongdaemun site’s memories from the Joseon dynasty through the relevant remains and exhibits, based on which this study investigated the aesthetic methodology of place exploration using three frameworks. The results acquired from the process are as follows: First, the Dongdaemun Design Plaza site was the heterotopia of opening and closing where functions were changed as a military strategic point in order to physically overcome topographic weakness. Second the water gate named “Igan” and rampart remains can be interpreted as the places where our ancestors continuously desired to cherish and protect the past Dongdaemun site. Lastly, the appearance of Gyeongseong Stadium in the past that was built as a sports complex by the Japanese Imperialism can be inferred as temporarily building utopia coordinated by the Japanese Imperialism during the Japanese colonial rule. While this study examined the aesthetics of form from previous studies reporting that the Dongdaemun Design Plaza building designed by Zaha Hadid has today’s de-constructivist’s nomadism characteristics, this study tried to investigate the proof on how it co-exists with contemporary landscape from the Baroque point of view in terms of art history. In conclusion, the Dongdaemun Design Plaza taking on such aesthetics of form can be regarded as a case of a utopian place built due to the politics of place nowadays.